Functional lung imaging in thoracic tumor radiotherapy: Application and progress - Zhou, Pi-Xiao; Zhang, Shu-Xu (Frontiers in Oncology, 2022)
Radiotherapy plays an irreplaceable and unique role in treating thoracic tumors, but the occurrence of radiation-induced lung injury limited the increase in tumor target doses and influenced patients' quality of life. However, the introduction of functional lung imaging has been incorporating functional lung into radiotherapy planning. By the design of the functional lung protection planning, while meeting the target dose requirements and dose limitations of the organs at risk (OARs), minimize the radiation dose to the functional lung, thus reducing the occurrence of radiation-induced lung injury. In this manuscript, we mainly reviewed the lung ventilation or/and perfusion functional imaging modalities, application, and progress, as well as the results based on the functional lung protection planning in thoracic tumors. In addition, we also discussed the problems that should be explored and further studied in the practical application of based on functional lung radiotherapy planning.